2014
DOI: 10.1123/kr.2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Online Pedagogy into Kinesiology: Service Learning for Kinesiology Majors

Abstract: Many universities have limited resources yet aim to provide worthy learning opportunities to their students. This goal can be met through the offering of alternative delivery methods and service learning. Alternative delivery methods have evolved as technology has advanced. This paper addresses the benefits of blended learning for students, faculty, and universities. Through an institutional grant emphasizing innovative teaching strategies, the authors explain how a kinesiology course that includes service lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…University policy for technology integration was raised as another issue. As universities provide online delivery mediums for organizing and administering online course information and assignments (Luke & Morrissey, 2014), support mechanisms should also be developed for blended learning opportunities such as organizational infrastructure, faculty development, and course development (Moskal et al, 2013). Research showed that training instructors for LMS make them more assessment and grade-oriented (Chow et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…University policy for technology integration was raised as another issue. As universities provide online delivery mediums for organizing and administering online course information and assignments (Luke & Morrissey, 2014), support mechanisms should also be developed for blended learning opportunities such as organizational infrastructure, faculty development, and course development (Moskal et al, 2013). Research showed that training instructors for LMS make them more assessment and grade-oriented (Chow et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With 3 appropriate planning and support, blended learning could lead to an encouraging transformation for faculty development and students' satisfaction with their learning experiences (Moskal et al, 2013). To effectively organize and administer online course information and assignments, universities provide online delivery mediums also referred to as Learning Management Systems (LMS) (Luke & Morrissey, 2014).…”
Section: Introductionmentioning
confidence: 99%